La concordia: la plaza de mercado como dispositivo estructurador del sector (2022)
Making an exit through the historic center of Bogotá, you can see the Plaza de Mercado La Concordia, which not only stands out for its architectural design, but also for being Cultural Heritage. Despite its importance and its history, the market place is not connected with its context, therefore, an analysis of the sector is carried out looking for the problems, a historical approximation is made through a time line, some references are studied to see the impact they generate on a heritage element in the sector and how they are linked through intervention strategies such as: identity, Hybrid Buildings, Public Space, language and Materiality. The analysis takes into account the entire regulatory framework, an approximation to the context and the location of the market place is made, a diagnosis of the territory is carried out by layers, the urban activity, the gastronomic corridors and the cultural corridor are analyzed and commercial. Subsequently, an exercise called "The street" is carried out to be able to understand the street and what happens in it, in this tour you begin to see all the urban phenomena that direct the route in order to understand the city from everyday life.